Effects of Contract Ambiguity in Interorganizational Governance. (July 2020) - Zheng, Xu (Vivian); Griffith, David A.; Ge, Ling; Benoliel, Uri
This work introduces the concept of contract ambiguity from the law literature into the interorganizational governance literature. Within the context of franchising, the authors present a three-study multimethod design empirically establishing the construct of contract ambiguity of franchisor obligations, providing new insights into the strategic design of contracts and their outcomes. In Study 1, the authors establish construct validity by demonstrating that contract ambiguity of franchisor obligations is distinct from contract specificity and contract completeness of franchisor obligations, with differential outcomes. In Studies 2 and 3, the authors demonstrate that contract ambiguity of franchisor obligations increases an interest-based (vs. a rights-based) conflict solving approach, implying greater cooperation and joint problem solving, and reduces franchisee-initiated litigation. The findings also indicate that while contract ambiguity of franchisor obligations decreases franchisee-initiated litigation, this effect is amplified by higher levels of franchisor training programs but mitigated by the presence of a franchisee association. The article closes with a discussion of implications for academics and practitioners.